MAIN COMPONENTS OF HOTEL ACTIVITIES IN THE TODAY’S CONDITIONS - Rumiantseva , I.B. (The actual problems of regional economy development, 2019)
In recent years, the accelerated development of the world hotel industry has followed. Expansion of the market of hotel services, quality service of rendering of hotel services, professionalism of the personnel, use of modern technologies in work of hotels, such tendency prevails in modern hotel business. The hotel industry has become one of the most dynamic businesses in the world. There is a rapid development of the latest technologies in the field of hotel business. This is due to the fact that when properly used, you can get the maximum effect for the hotel business. Modern technologies allow to organize the work of hotel enterprises with maximum efficiency. Provision of quality services in the hotel enterprise ultimately serves to increase the profitability of the enterprise and prestige of the hotel. The latest technologies in the hotel business include: information technology, automation of all processes of the hotel enterprise, various trainings and staff training. The hotel business has become so versatile that it requires the use of a variety of modern technologies. The purpose of the article is to investigate the main components of the hotel enterprise in the present conditions, to analyze the hotel services provided, to determine the role of information technology in modern hotels. The article analyzes the activity of hotels in modern conditions of management. The main components that improve the activity of the modern hotel enterprise are given. The automation of the processes of the hotel enterprise, the training of hotel employees, the use of modern information technologies are offered.